2013
DOI: 10.1021/ja404422z
|View full text |Cite
|
Sign up to set email alerts
|

DNA Switches on the Two-Photon Efficiency of an Ultrabright Triphenylamine Fluorescent Probe Specific of AT Regions

Abstract: We report on the design and synthesis of two-photon fluorescent triphenylamines bearing two or three vinyl branches terminated by a N-methyl benzimidazolium moiety. The new compounds (TP-2Bzim, TP-3Bzim) are light-up fluorescent DNA probes with a long wavelength emission (>580 nm). Compared to their pyridinium models, the TP-Bzim dyes exhibit a remarkable improvement of both their DNA affinity and fluorescence quantum yield, especially for the two-branch derivative (TP-2Bzim: ΦF = 0.54, Ka = 10(7) M(-1)), resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
72
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(80 citation statements)
references
References 61 publications
4
72
0
1
Order By: Relevance
“…[11][12][13][14][15] Compared with these techniques,fluorescence imaging methods assisted with proper fluorescent probes have received considerable interest in recent years,o wing to the unique advantages including capability of in situ and real-time visualization in live cells,l ow damage to biosamples,a nd permission of dynamically analyzing live samples. [19] Eliseeva et al have presented an ear infrared fluorescent probe for the discrimination of dead cells. [18] Te ulade-Fichou and co-workers have developed two-photon fluorescent probes for the imaging of cell nucleus.…”
mentioning
confidence: 99%
“…[11][12][13][14][15] Compared with these techniques,fluorescence imaging methods assisted with proper fluorescent probes have received considerable interest in recent years,o wing to the unique advantages including capability of in situ and real-time visualization in live cells,l ow damage to biosamples,a nd permission of dynamically analyzing live samples. [19] Eliseeva et al have presented an ear infrared fluorescent probe for the discrimination of dead cells. [18] Te ulade-Fichou and co-workers have developed two-photon fluorescent probes for the imaging of cell nucleus.…”
mentioning
confidence: 99%
“…[11][12][13][14] Recently, Teulade-Fichou et al reported a nuclear membrane permeable DNA-selective TPEF probe which bound to duplex DNA in nucleus due to its relatively strong interaction with DNA at the AT-rich region. 15 This probe allowed the investigation of the transcriptional dynamics of the cell nucleus. However, a nuclear RNAselective TPEF probe for live cell imaging is rarely available.…”
mentioning
confidence: 99%
“…20 So far, a number of two-photon probes have been studied for cellular DNA or other organelles targeting and imaging. [21][22][23][24][25] However, studies involving organic small-molecule probes targeting cellular nucleus for the long-term monitoring and tracking are rarely reported. 26,27 Thus, extreme attention should be paid to nucleus monitoring for the enhancement of photostability in biomedical imaging.…”
Section: Introductionmentioning
confidence: 99%